RNF4-Dependent Oncogene Activation by Protein Stabilization - Jane Joy Thomas; Mona Abed; Julian Heuberger; Rostislav Novak; Yaniv Zohar; Ángela Patricia Beltrán López; Julie S. Trausch‐Azar; Ma. Xenia G. Ilagan; David Benhamou; Gunnar Dittmar; Raphael Kopan; Walter Birchmeier; et al. (2016)
Ubiquitylation regulates signaling pathways critical for cancer development and, in many cases, targets proteins for degradation. Here, we report that ubiquitylation by RNF4 stabilizes otherwise short-lived oncogenic transcription factors, including β-catenin, Myc, c-Jun, and the Notch intracellular-domain (N-ICD) protein. RNF4 enhances the transcriptional activity of these factors, as well as Wnt- and Notch-dependent gene expression. While RNF4 is a SUMO-targeted ubiquitin ligase, protein stabilization requires the substrate's phosphorylation, rather than SUMOylation, and binding to RNF4's arginine-rich motif domain. Stabilization also involves generation of unusual polyubiquitin chains and docking of RNF4 to chromatin. Biologically, RNF4 enhances the tumor phenotype and is essential for cancer cell survival. High levels of RNF4 mRNA correlate with poor survival of a subgroup of breast cancer patients, and RNF4 protein levels are elevated in 30% of human colon adenocarcinomas. Thus, RNF4-dependent ubiquitylation translates transient phosphorylation signal(s) into long-term protein stabilization, resulting in enhanced oncoprotein activation.